Tin-based catalyst and application thereof in synthesis of formic acid by electrocatalytic conversion of carbon dioxide
By doping single-atom rare earth elements into the tin-based catalyst to form a rare earth element-doped tin-based catalyst, the problems of low catalytic activity and poor selectivity of existing electrocatalysts in carbon dioxide reduction reaction are solved, and efficient and stable preparation of formic acid is achieved, achieving industrial current density requirements.
Patent Information
- Application Number
- CN202411685071.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-18
AI Technical Summary
The existing electrocatalysts have low activity, poor selectivity and insufficient stability in the carbon dioxide reduction reaction, making it difficult to meet industrial needs.
By doping rare earth elements in the form of a single atom into the tin-based catalyst, a tin-based catalyst doped with rare earth elements is formed, and the catalyst is prepared by solvothermal method, and the electrode is supported for electrocatalytic reaction.
The formic acid selectivity and catalytic activity of tin-based catalysts are improved, the current density meets the requirements of industrial current density, and has the ability to efficiently and stably electrocatalytically reduce carbon dioxide to prepare formic acid.
Smart Images

Figure CN119640323A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrochemical conversion, and in particular to a tin-based catalyst and application thereof in electrocatalytic conversion of carbon dioxide to formic acid. Background Art
[0002] Carbon dioxide reduction reaction (CO 2 RR) technology is a technology that converts greenhouse gas carbon dioxide into value-added hydrocarbon products. It is considered a promising strategy to address energy challenges and also provides a potential solution to alleviate environmental problems. However, in general, CO 2 During the RR reaction, multiple competing reactions occur simultaneously, producing a variety of potential products, including hydrogen, carbon monoxide, formic acid, methanol, methane, ethylene, etc. Among the many reaction products, formic acid (HCOOH) is a liquid product with high energy density, which is easy to store and transport. In addition, formic acid can be used as a hydrogen carrier in fuel cells in the battery field. In addition, formic acid also has many applications in other fields such as medicine. However, at present, CO 2 The RR process of formic acid production faces many challenges, such as low catalyst activity, poor selectivity, and insufficient stability. Therefore, it is of great significance to develop a catalyst with high catalytic activity and high formic acid selectivity for the electrocatalytic conversion of carbon dioxide to formic acid.
[0003] So far, the highly selective and active electrocatalysts developed for the production of formic acid are mainly concentrated on metal-based materials, such as Hg, Pb, In, Sn, Bi, etc. Among the many metal-based materials, tin-based materials have become a research feature that has attracted much attention due to their high cost-effectiveness, abundant reserves, non-toxicity, and strong catalytic activity. 2 The activity of RR and the selectivity of formic acid generation are greatly limited by the high energy barrier, which is closely related to the weak binding energy of the *OCHO intermediate at the Sn site. The incorporation of heteroatoms to modulate the electronic structure of the active site is believed to promote the CO 2 A powerful strategy for improving RR performance. Rare earth elements have significant advantages in catalyst modification due to their unique electronic structure and physicochemical properties, but their application in tin-based materials has not been widely explored. Single-atom catalysts have the advantage of high atomic utilization, and there are currently no reports on single-atom rare earth element-doped Sn-based catalysts for electrocatalytic production of formic acid from carbon dioxide. Summary of the invention
[0004] The invention provides a tin-based catalyst, which can efficiently electrocatalyze carbon dioxide to produce formic acid and has high selectivity for formic acid.
[0005] The present invention also provides an electrode for electrocatalytically converting carbon dioxide into formic acid, wherein when the potential is -1.0 V vs. RHE, the current density is greater than 300 mA cm -2 , reaching the industrial current density requirements (>200mA cm -2 ).
[0006] The present invention also provides a method for synthesizing formic acid by electrocatalytic conversion of carbon dioxide, which can prepare formic acid by electrocatalytic reduction of carbon dioxide with high efficiency and high stability.
[0007] The present invention achieves the above technical objectives through the following technical solutions:
[0008] The present invention provides a tin-based catalyst. The tin-based catalyst is doped with a rare earth element. The rare earth element is doped in the tin-based catalyst in the form of a single atom. In the tin-based catalyst, tin exists in the form of tin dioxide.
[0009] In the above-mentioned tin-based catalyst, the rare earth element is selected from one or more of lanthanum, praseodymium, neodymium, europium, erbium and scandium.
[0010] The tin-based catalyst described above is prepared from a tin compound and a rare earth element compound by a solvent thermal method.
[0011] The tin-based catalyst described above further comprises the steps of separating and drying the precipitate in the reaction system after the solvothermal reaction is completed.
[0012] In the above-mentioned tin-based catalyst, the tin compound is selected from at least one of tin sulfate, tin nitrate, tin chloride, tin acetate and hydrates thereof.
[0013] In the above-mentioned tin-based catalyst, the rare earth element compound is selected from at least one of rare earth metal chlorides, rare earth metal nitrates, rare earth metal acetates, rare earth metal sulfates and hydrates thereof.
[0014] According to the tin-based catalyst described above, the solvent used in the solvothermal reaction is selected from at least one of ethanol, ethylene glycol, acetone and acetonitrile.
[0015] According to the above-mentioned tin-based catalyst, the molar ratio of the tin compound to the rare earth element compound is 100:0.1-20.
[0016] With the tin-based catalyst described above, the temperature of the solvent thermal reaction is 100-300° C., and the reaction time is 3-24 hours.
[0017] The present invention also provides an electrode for synthesizing formic acid by electro-conversion catalysis of carbon dioxide, on which the above-mentioned tin-based catalyst is loaded.
[0018] The present invention also provides a method for synthesizing formic acid by electro-conversion catalytic carbon dioxide, comprising the steps of using carbon dioxide as a raw material and the above-mentioned tin-based catalyst as a catalyst for catalytic conversion.
[0019] The preparation method described above utilizes constant potential electrolysis, uses carbon dioxide as raw material, and synthesizes formic acid by electrolytic reaction in an electrolytic cell reaction device through the action of electrodes and electrolyte, and the tin-based catalyst is located on the surface of the electrode material.
[0020] According to the preparation method described above, the electrolyte is selected from KOH aqueous solution, KHCO 3 Aqueous solution, KCl aqueous solution, NaOH aqueous solution, NaHCO 3 At least one of an aqueous solution and a NaCl aqueous solution.
[0021] The present invention effectively improves the formic acid selectivity of the tin-based catalyst by doping the rare earth element in the form of single atoms in the tin-based catalyst, and the current density of the electrode loaded with the rare earth element can meet the industrial current density requirement under the condition of a potential of -1.0V vs.RHE.
[0022] The method for synthesizing formic acid by electro-conversion catalytic carbon dioxide provided by the present invention can obtain formic acid efficiently and stably, and has potential industrial value. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The catalyst (La-SnO 2 ) of the scanning electron microscope;
[0024] Figure 2 The catalyst (La-SnO 2 )’s X-ray diffraction analysis pattern;
[0025] Figure 3 The catalyst (La-SnO 2 )’s element distribution diagram;
[0026] Figure 4 The catalyst (La-SnO 2 )'s spherical aberration electron microscope image;
[0027] Figure 5 The catalyst (La-SnO 2 ) and SnO 2 Faradaic efficiency diagram of the catalyst for electrochemical reduction of carbon dioxide to formic acid;
[0028] Figure 6The catalyst (La-SnO 2 ) and SnO 2 Formic acid current density diagram for electrochemical reduction of carbon dioxide to formic acid by the catalyst;
[0029] Figure 7 is a Faraday efficiency diagram of the electrochemical reduction of carbon dioxide to formic acid by Sn-based catalysts with different La doping amounts in Example 2;
[0030] Figure 8 is a graph of formic acid current density for electrochemical reduction of carbon dioxide to formic acid using Sn-based catalysts with different La doping amounts in Example 2;
[0031] Fig. 9 The catalyst (Nd-SnO 2 ) Faradaic efficiency diagram for electrochemical reduction of carbon dioxide to formic acid;
[0032] Fig.10 The catalyst (Er-SnO 2 ) Faradaic efficiency diagram for electrochemical reduction of carbon dioxide to formic acid;
[0033] Fig.11 The catalyst (La-SnO 2 )’s stability test diagram. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] The present invention provides a tin-based catalyst, wherein the tin-based catalyst is doped with a rare earth element, wherein the rare earth element is doped in the tin-based catalyst in a single-atom form, and the tin in the tin-based catalyst exists in the form of tin dioxide. By doping the tin-based catalyst with a single-atom rare earth element, the tin-based catalyst has better formic acid selectivity and catalytic activity.
[0036] Furthermore, the rare earth element is selected from one or more of lanthanum (La), praseodymium (Pr), neodymium (Nd), europium (Eu), erbium (Er), and scandium (Sc).
[0037] Specifically, the tin-based catalyst can be prepared from a tin compound and a rare earth element compound by a solvothermal method. Detection of the reaction products shows that the rare earth element is doped in the tin-based catalyst in the form of a single atom, and tin exists in the form of tin dioxide.
[0038] The solvothermal method described in the present invention is a chemical reaction method known in the art, which is developed on the basis of the hydrothermal method, and refers to a synthesis method in which the original mixture reacts in a closed system such as an autoclave, with an organic or non-aqueous solvent as a solvent, at a certain temperature and the autogenous pressure of the solution. The difference between the solvothermal method and the hydrothermal reaction is that the solvent used is an organic substance instead of water. In the present invention, since the rare earth element is sensitive to water and can react with water, the doping of the rare earth element is achieved by the solvothermal method.
[0039] After the solvothermal reaction is completed, the precipitate in the reaction system is separated and dried to obtain the target product, the tin-based catalyst. The separation and drying method of the precipitate is not particularly limited, and conventional separation and drying methods can be used, such as centrifugation, washing, oven drying, etc. For example, in some specific embodiments, the precipitate is separated by centrifugation at 3000-11000 rpm for 1-60 minutes, and then washed with ethanol, acetone or methanol, and dried at 30-120° C. for 1-48 hours.
[0040] In the present invention, there is no particular restriction on the selection of tin compounds and rare earth element compounds. For example, the tin compound can be selected from at least one of tin sulfate, tin nitrate, tin chloride, tin acetate and hydrates thereof, and the rare earth element compound can be selected from at least one of rare earth metal chlorides, rare earth metal nitrates, rare earth metal acetates, rare earth metal sulfates and hydrates thereof.
[0041] The solvent used in the solvothermal reaction is at least one selected from ethanol, ethylene glycol, acetone and acetonitrile.
[0042] During the solvothermal reaction, the molar ratio of the tin compound to the rare earth element compound is 100:0.1-20, preferably 100:10.
[0043] During the solvent thermal reaction, the reaction temperature is 100-300°C and the reaction time is 3-24 hours. The preferred reaction temperature is 220°C and the reaction time is 6 hours.
[0044] The present invention also provides an electrode for electrocatalytic conversion of carbon dioxide into formic acid, the electrode being loaded with the above-mentioned tin-based catalyst. The electrode has a current density greater than 300 mA cm at a potential of -1.0 V vs. RHE. -2 , reaching the industrial current density requirements (>200mA cm -2 ).
[0045] More specifically, the preparation method of the electrode can adopt a conventional electrode preparation method. For example, in some specific embodiments, it can be prepared by the following method: dispersing a tin-based catalyst in an organic solvent, and adding a Nafion D-520 dispersion as a binder to obtain a dispersion; and dropwise coating the dispersion on a gas diffusion layer to obtain the electrode.
[0046] The organic solvent is selected from at least one of acetone, ethanol, isopropanol and methanol, and the ratio of Nafion D-520 dispersion to tin-based catalyst can be 5-50 μL:2 mg, preferably 15 μL:2 mg. The gas diffusion layer can be selected from at least one of carbon fiber paper with PTFE coating, carbon fiber woven cloth and carbon black paper.
[0047] The loading amount of tin-based catalyst is 0.1~100mg·cm -2 The preferred loading is 1 mg cm -2 .
[0048] The present invention also provides a method for synthesizing formic acid by electrocatalytic conversion of carbon dioxide, which comprises the steps of using carbon dioxide as a raw material and the above-mentioned tin-based catalyst as a catalyst for catalytic conversion.
[0049] More specifically, the method is: using constant potential electrolysis, taking carbon dioxide as raw material, and synthesizing formic acid by electrolytic reaction in an electrolytic cell reaction device through the action of electrodes and electrolyte.
[0050] In the above method, the electrolyte is a conventional electrolyte, such as KOH aqueous solution, KHCO 3 Aqueous solution, KCl aqueous solution, NaOH aqueous solution, NaHCO 3 The concentration of aqueous solution and NaCl aqueous solution is usually 0.1-10M.
[0051] The specific electrolytic cell reaction device is not limited, for example, an H-type electrolytic cell or a flow-type electrolytic cell can be selected. The potential of the electrolytic reaction can be -0.4 to -2.4 V vs. RHE.
[0052] The tin-based catalyst of the present invention and its application are described in detail below in conjunction with specific implementation methods.
[0053] Example 1
[0054] First, La(NO 3 ) 3 6H 2 O and SnCl 4 ·5H 2O was ultrasonically dissolved in 30 mL of ethanol solution and stirred vigorously for 1 h. The obtained mixed solution was placed in a 50 mL hydrothermal kettle and kept at 220 ° C for 6 h. After cooling to room temperature naturally, centrifuged at 10000 rpm for 5 min to obtain a precipitate. After washing with ethanol, the obtained precipitate was placed in a vacuum drying oven at 60 ° C for 16 h to obtain La-SnO 2 catalyst.
[0055] By adjusting La(NO 3 ) 3 6H 2 O and SnCl 4 ·5H 2 O addition ratio, respectively, to obtain 2.7% La-SnO 2 , 3.2% La-SnO 2 , 5.7% La-SnO 2 、6.5% La-SnO 2 The mass fraction of the elements in the catalyst was measured by inductively coupled plasma emission spectrometry, and the corresponding La(NO 3 ) 3 6H 2 O and SnCl 4 ·5H 2 O added were: 0.025mmol La(NO 3 ) 3 6H 2 O and 1 mmol SnCl 4 ·5H 2 O(2.7% La-SnO 2 )、0.05mmol La(NO 3 ) 3 6H 2 O and 1mmolSnCl 4 ·5H 2 O(3.2% La-SnO 2 )、0.10mmol La(NO 3 ) 3 6H 2 O and 1 mmol SnCl 4 ·5H 2 O(5.7% La-SnO 2 )、0.15mmol La(NO 3 ) 3 6H 2 O and 1 mmol SnCl 4 ·5H 2 O(6.5% La-SnO 2 ).
[0056] For comparison, SnO was synthesized according to the above method without adding rare earth metal compounds. 2 catalyst.
[0057] The catalyst (La-SnO 2 ) as an example, for La-SnO 2 The catalyst was systematically characterized. Figure 1 is a scanning electron microscope (SEM) image. Figure 2 is the X-ray diffraction analysis (XRD) diagram, Figure 3 is the element distribution (EDSMapping) diagram, Figure 4 This is a spherical aberration electron microscope (HAADF-STEM) image. Figure 1 It can be seen that La-SnO 2 The catalyst morphology is spherical; Figure 2 It can be seen that La-SnO 2 Sn in the catalyst exists in the form of tin dioxide; Figure 3 It can be seen that Sn, La, and O elements are evenly distributed on the catalyst surface; Figure 4 It can be seen that La element is doped in the Sn-based catalyst in the form of single atoms.
[0058] The SnO prepared above 2 Catalyst structure and La-SnO 2 Similar, but only Sn and O elements are evenly distributed on the catalyst surface.
[0059] Example 2
[0060] Preparation of working electrode: A catalyst (La-SnO 2 ) as an example, first 2 mg La-SnO 2 The catalyst was dispersed in 0.7 mL of isopropanol together with 15 μL of Nafion D-520 dispersion (5 wt%) and dispersed evenly under ultrasonication for 30 min. The dispersion was evenly drop-coated on the surface of the carbon fiber paper of the gas diffusion layer and allowed to stand at room temperature for 12 h to obtain a working electrode, wherein the catalyst loading on each electrode was 1 mg cm -2 .
[0061] The electrolysis experiment was carried out at 25°C. The electrolytic cell device used was a three-electrode flow-type electrolytic cell system. The three electrodes included the above-mentioned working electrode, a Pt sheet counter electrode, and a Hg / HgO reference electrode. A 1M KOH aqueous solution was added, and a Fumasep FAA-3-PK-130 membrane was used as an anion exchange membrane to separate the cathode and the anode. A 1M KOH aqueous solution was used as the electrolyte in the anode and cathode chambers, and the electrolyte dosage was 20 mL. 2The flow rate was controlled at 40 sccm, the potential range was -0.7 to -1.2 V vs. RHE, and the electrolysis time was 0.5 h. The gaseous products were collected using a gas bag and analyzed by a gas chromatograph (GC, HP4890D), and the liquid products were analyzed by a liquid chromatograph (GC, 2014AFSC).
[0062] Electrocatalytic CO under different catalytic conditions 2 The test results of the reaction are as follows Figure 5 , Figure 6 As shown in the figure, the catalytic system of the present invention has excellent formic acid selectivity (Faraday efficiency greater than 90%) and high formic acid separation current density. When the potential is -1.0V vs. RHE, its current density is greater than 300mA cm -2 , reaching the industrial current density requirements (>200mA cm -2 ), and its activity is much higher than SnO 2 The catalytic activity of Sn-based catalysts with different La doping amounts in the electrocatalytic CO 2 The test results of the reaction are as follows Figure 7 , Figure 8 As shown in the figure, it can be seen that when the molar ratio of the lanthanum compound to the tin compound is 0.1, the activity of generating formic acid is optimal.
[0063] Example 3
[0064] The difference between this embodiment and embodiment 1 is that Nd(NO 3 ) 3 6H 2 O replaces La(NO 3 ) 3 6H 2 O was used to prepare Nd-SnO with a Nd mass fraction of 5.7%. 2 The catalyst was then tested according to the method described in Example 2. The test results are as follows Fig. 9 shown.
[0065] Example 4
[0066] The difference between this embodiment and embodiment 1 is that Er(NO 3 ) 3 ·5H 2 O replaces La(NO 3 ) 3 6H 2 O was used to prepare Er-SnO with Er mass fraction of 5.7%. 2 The catalyst was then tested according to the method described in Example 2. The test results are as follows Fig.10 shown.
[0067] Example 5
[0068] According to the method described in Example 2, the catalyst (La-SnO 2 ) long-term stability, such as Fig.11 As shown, at 400mA cm -2 The reaction was carried out for about 45 hours at a constant current density of . The results showed that there was no significant change in the applied potential and the Faradaic efficiency of formic acid, indicating that the catalyst has good electrochemical stability and potential industrial value.
[0069] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A tin-based catalyst, characterized in that The tin-based catalyst is doped with a rare earth element, and the rare earth element is doped in the tin-based catalyst in the form of a single atom. The tin in the tin-based catalyst exists in the form of tin dioxide.
2. The tin-based catalyst according to claim 1, characterized in that The rare earth element is selected from one or more of lanthanum, praseodymium, neodymium, europium, erbium and scandium.
3. The tin-based catalyst according to claim 1 or 2, characterized in that The tin-based catalyst is prepared from a tin compound and a rare earth element compound by a solvent thermal method.
4. The tin-based catalyst according to claim 3, characterized in that The method also includes the steps of separating and drying the precipitate in the reaction system after the solvothermal reaction is completed.
5. The tin-based catalyst according to claim 3, characterized in that The tin compound is selected from at least one of tin sulfate, tin nitrate, tin chloride, tin acetate and hydrates thereof; and / or The rare earth element compound is selected from at least one of rare earth metal chlorides, rare earth metal nitrates, rare earth metal acetates, rare earth metal sulfates and hydrates thereof; and / or The solvent used in the solvothermal reaction is selected from at least one of ethanol, ethylene glycol, acetone and acetonitrile.
6. The tin-based catalyst according to claim 3, characterized in that The molar ratio of the tin compound to the rare earth element compound is 100:0.1-20; and / or The solvent thermal reaction temperature is 100-300° C., and the reaction time is 3-24 hours.
7. An electrode for electrocatalytic conversion of carbon dioxide into formic acid, characterized in that: The electrode is loaded with the tin-based catalyst described in any one of claims 1 to 6.
8. A method for synthesizing formic acid by electrocatalytic conversion of carbon dioxide, characterized in that: The method comprises the steps of using carbon dioxide as raw material and carrying out catalytic conversion using the electrode described in claim 7.
9. The method for synthesizing formic acid by electrocatalytic conversion of carbon dioxide according to claim 8, characterized in that: The method utilizes constant potential electrolysis method, uses carbon dioxide as raw material, and conducts electrolytic reaction in an electrolytic cell reaction device through the action of electrodes and electrolyte to synthesize formic acid.
10. The method for synthesizing formic acid by electrocatalytic conversion of carbon dioxide according to claim 8 or 9, characterized in that: The loading amount of the tin-based catalyst on the electrode is 0.1 to 100 mg cm -2 ; and / or The electrolyte is selected from at least one of a KOH aqueous solution, a KHCO3 aqueous solution, a KCl aqueous solution, a NaOH aqueous solution, a NaHCO3 aqueous solution and a NaCl aqueous solution.